GAMBARAN PENGETAHUAN IBU MENYUSUI TENTANG ASI ESKLUSIF - Sindi Sindi; Anna Yuliastani Pomalingo; Sofyawati Talibo (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2021)
Exclusive breastfeeding is to give only breast milk without giving other food and drinks to babies from birth to 6 months of age, except for drugs or vitamins. However, it does not mean that after exclusive breastfeeding, breastfeeding is stopped, but it is still given to babies until the baby is 2 years old. The study aims to determine the description of breastfeeding mothers' knowledge about exclusive breastfeeding in Talango Village, Kabila District, Bone Bolango Regency. The type of research was a descriptive survey research. The number of samples was 26 samples. The research variable is the independent variable describing the mother's knowledge about exclusive breastfeeding. The results of the study were the knowledge of breastfeeding mothers, regarding exclusive breastfeeding is more in the good category with a total of 16 people with a percentage of 61.2% and the respondents in the sufficient category are 10 people, the most respondents according to age are 28-33 years old. amounted to 14 people with a percentage of 53.8%. For respondents according to occupation, most of them are IRT with a total of 22 people with a percentage of 84.6. Then respondents according to education more junior high school education with a total of 8 people with a percentage of 30.8%. The conclusion of the study was breastfeeding mothers with exclusive breastfeeding from 26 respondents showed that respondents who had good knowledge were 16 people with a percentage (61.2%) and those who had sufficient knowledge were 10 people with a percentage (38.5%).ASI eksklusif adalah memberikan hanya ASI saja tanpa memberikan makanan dan minuman lain kepada bayi sejak lahir sampai berusia 6 bulan, kecuali obat atau vitamin. Namun bukan berarti setelah pemberian ASI eksklusif pemberian ASI dihentikan, akan tetapi tetap diberikan kepada bayi sampai bayi berusia 2 tahun. Tujuan penelitian untuk mengetahui Gambaran Pengetahuan Ibu menyusui tentang ASI esklusif di Desa Talango Kecamatan Kabila Kabupaten Bone Bolango. Metode penelitian adalah penelitian kuantitatif dengan metode survey deskriptif, untuk melihat gambaran pengetahuan ibu menyusui tentang ASI eksklusif di desa Talango. Hasil penelitian menunjukkan pengetahun ibu menyusui tentang ASI eskluisf lebih banyak kategori baik dengan jumlah 16 orang dengan presentase 61,2% dan responden kategori cukup berjumlah 10 orang, responden menurut usia terbanyak yaitu beusia 28-33 tahun yang berjumlah 14 orang dengan presentase 53,8%. Untuk responden menurut pekerjaan terbanyak IRT dengan jumlah 22 orang dengan presentase 84,6. Kemudian responden menurut pendidikan lebih banyak berpendidikan sekolah menengah pertama dengan jumlah 8 orang dengan presentase 30,8%. Kesimpulan penelitian yaitu ibu menyusui pengetahuan tentang ASI esklusif dari 26 responden menunjukan bahwa responden yang pengetahuannya baik berjumlah 16 orang dengan presentase (61,2%) dan yang memiliki pengetahuan cukup berjumlah 10 orang dengan presentase (38,5%).